Selecting Fuchs Patients for Drug Trials Involving Endothelial Cell Proliferation. Issue 6 (November 2016) - Shearer, Thomas R.; Chamberlain, Winston D.; Fujii, Atsuko; Azuma, Mitsuyoshi
Purpose: Fuchs endothelial corneal dystrophy (FECD) might be managed by drug treatment before becoming severe enough to require surgery. For a clinical trial of such a drug, we hypothesize that selecting an adequate number of patients with FECD with only moderately compromised cell densities will be challenging. Thus, the purpose of the present study was to measure the prevalence of patients with FECD exhibiting moderately decreased corneal cell densities. Methods: A retrospective data mining study (cross-sectional study) was performed on patient charts presenting at a large US northwestern academic health center by searching for diagnosis ICD-9 code 371.57 and Fuchs corneal dystrophies, including those with prior cataract surgeries and/or existing glaucoma. Patients with prior corneal transplants were excluded. Noncontact specular photomicroscopic data (Topcon 2000) were obtained from the central region whenever possible, and individual eyes were grouped according to cell density (cells/mm 2 ): severe (<800), moderate (800-1, 500), and mild (>1, 500). Results: The values for 98 eyes from 61 patients with FECD were as follows (mean ± SD): corneal thickness 573 ± 59 μm, cell size 627 ± 336 μm 2 /cell, coefficient of variation 23 ± 7, and density 1, 883 ± 703 cells/mm 2 . The moderate subgroup with cell density values averaging 1, 184 ± 212 (26) comprised 27% of the total FECD patient pool. Conclusions: Only approximately 1 out of 4 patients with FECD will show moderately compromised corneal cell densities. A moderate level of damage may be optimal for clinical trials for testing topical drugs on endothelial cell viability. Thus, investigators will need to initially screen a fourfold excess of all patients with FECD.